2003
DOI: 10.1079/bjn2003862
|View full text |Cite
|
Sign up to set email alerts
|

Effects of goats' or cows' milks on nutritive utilization of calcium and phosphorus in rats with intestinal resection

Abstract: We analysed the effects of goats' milk (GM) on the nutritive utilization of Ca and P in rats with resection of 50 % distal small intestine in comparison with cows' milk (CM) and a standard non-milk diet. The three test diets contained 200 g protein and 100 g fat/kg. The apparent digestibility coefficient (ADC) of Ca and P were considerably higher in the two groups of rats given the GM diet than those given the other two diets. Ca and P retention did not decrease by effect of intestinal resection with GM diet. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Furthermore, the lesser Ca-Fe interaction might partly explain the particular nutritional characteristics of G diet with respect to C diet (Alfe´rez et al, 2006;Barrionuevo et al, 2002;Campos et al, 2003).…”
Section: Article In Pressmentioning
confidence: 97%
“…Furthermore, the lesser Ca-Fe interaction might partly explain the particular nutritional characteristics of G diet with respect to C diet (Alfe´rez et al, 2006;Barrionuevo et al, 2002;Campos et al, 2003).…”
Section: Article In Pressmentioning
confidence: 97%
“…Similarly, the fat of goat milk is more digestible (Alfé rez et al, 2001;Haenlein, 2001), and it may be considered an excellent source of energy for use in various metabolic processes (Boza and Sanz Sampelayo, 1997;Sanz Ceballos, 2007) and even for combating metabolic diseases (Babayan, 1981;García Unciti, 1996;Velá zquez et al, 1996). With respect to its mineral composition, in general the levels measured of the principal elements, and the nutritional use made of them, show it to be of higher quality than cow milk (Moreno, 1995;Boza and Sanz Sampelayo, 1997;Haenlein, 2001;Campos et al, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…Similarly, Campos et al 10 showed that goat milk improves mineral retention in rats with intestinal resection. In that study, goat milk was compared with a non-milk diet as well as cow milk.…”
Section: Discussionmentioning
confidence: 95%
“…4,5 Several animal-based studies have also indicated enhanced protein, mineral and fat utilisation from goat milk compared with cow milk. 6 -10 Studies also demonstrate a higher calcium content of the femur, sternum and Longissimus dorsi muscle 7,10 and higher bone mineral density 6 following consumption of goat milk compared with cow milk. The constituents or synergistic relationships in goat milk contributing to these benefits are not known.…”
Section: Introductionmentioning
confidence: 95%